A Four-Session Sleep Intervention Program Improves Sleep for Older Adult Day Health Care Participants: Results of a Randomized Controlled Trial. Issue 8 (6th May 2017) - Martin, Jennifer L; Song, Yeonsu; Hughes, Jaime; Jouldjian, Stella; Dzierzewski, Joseph M.; Fung, Constance H; Rodriguez Tapia, Juan Carlos; Mitchell, Michael N.; Alessi, Cathy A
Abstract: Study Objective: To test the effectiveness of a 4-week behavioral Sleep Intervention Program (SIP: sleep compression, modified stimulus control, and sleep hygiene) compared to a 4-week information-only control (IC) among older adults attending a VA Adult Day Health Care (ADHC) program in a double-blind, randomized, clinical trial. Methods: Forty-two individuals (mean age: 77 years, 93% male) enrolled in a VA ADHC program were randomized to receive SIP or IC. All completed in-person sleep and health assessments at baseline, post-treatment and 4-months follow-up that included 3 days/nights of wrist actigraphy, the Pittsburgh Sleep Quality Index (PSQI), and the Insomnia Severity Index (ISI). Mixed repeated measures analysis was used to compare sleep outcomes at post-treatment and 4-months follow-up, with baseline values as covariates. Results: SIP participants ( n = 21) showed significant improvement on actigraphy sleep efficiency ( p = .007), number of nighttime awakenings ( p = .016), and minutes awake at night ( p = .001) at post-treatment, compared to IC participants ( n = 21). Benefits were slightly attenuated but remained significant at 4-month follow-up (all p 's < .05). There were no differences in total sleep time between groups. There was significant improvement on PSQI factor 3 (daily disturbances) at 4-month follow-up ( p = .016), but no differences were observed between SIP and IC on other PSQI components or ISI scores at post-treatment or 4-month follow-up. Conclusions: A short behavioral sleep intervention may have important benefits in improving objectively measured sleep in older adults participating in ADHC. Future studies are needed to study implementation of this intervention into routine clinical care within ADHC.